The Donatist Circumcellions - Beaver, R. Pierce (Church history, 1935)
Donatism was an exclusively African schism and for more than a century held the center of the stage in the Christian life of that land. It was born of local passions and quarrels, and had no success outside of Africa. It became the church of the native population and, raising“altar against altar,”1 successfully opposed both the Catholic church and the Roman Empire during several generations. Frequently, and especially in Numidia, the church of Donatus was more numerous, richer, and more powerful than its Catholic neighbor. Moreover, the Donatist cause came to shelter under its name a true social and economic revolt, which it found a useful instrument at times, but which was never a recognized part of its policy. Although the Donatist controversy was thus a local schism, it had important results for the Latin church, chiefly in regard to the doctrine of the sacrament of baptism, the orders and reception of schismatics and heretics, and the coercion of non-Catholics.